Best Paper Award First Place "A Comparative study of explainable AI models in the assessment of multiple sclerosis" - Loizou, Christos P. (My University, 2026)
A. Nicolaou, C. S. Pattichis, A. Kakas, N. Prentzas, C. P. Loizou, M. Pantzaris, “A Comparative study of explainable AI models in the assessment of multiple sclerosis”, IEEE Int. Conf. on Biomed. and Health Informatics (BHI'23), pp. 1-4, Pittsburgh, Pennsylvania, 15-18 Oct. 2023.
Keywords: Sciences